The Possibility of Replacing Wet-Milling with Dry-Milling in the Production of Waxy Rice Flour for the Application in Waxy Rice Ball - Fang, Sicong; Chen, Maoshen; Xu, Feifei; Liu, Fei; Zhong, Fang (Foods, 2023)
Due to the large consumption and discharge of water in wet milling, dry-milling is an alternative to produce waxy rice flour. The physical properties and sensory characteristics for preparing waxy rice balls in dry-milled waxy rice flour were compared in this study. The results showed that the damaged starch content increased significantly with the particle size of dry-milled flour, which decreased from 160 to 30 μm. The reduction in particle size increased the pasting viscosity of waxy rice flour, which further improved the stretch ability of dough and increased the viscoelasticity of the rice ball. The increase in damaged starch content directly led to a significant increase in the solubility of dry-milled flour, thereby increasing the freeze cracking rate of the rice ball and reducing its transparency, resulting in a decline in quality. In comparison with wet-milled waxy rice balls, dry-milled waxy rice balls made from rice flour in the range of 40 μm to 60 μm particle size had a similar texture and taste to that of wet-milled ones, moderate freeze cracking rate and better storage stability, as well as a stronger aroma of waxy rice that the consumer favored. GC-MS analysis showed that the content of key aroma compounds, such as grassy and fruity, noted nonanal in dry-milled flour, was 15–30% higher than that in the wet-milled depending on the difference of waxy rice variety. In conclusion, dry-milled waxy rice flour with a particle size in the range of 40 μm to 60 μm could be a candidate to replace wet-milled flour in the preparation of a waxy rice ball.